"Alphabets of Flesh": Writing the Body and Diasporic Women's Autobiography in Meena Alexander's Fault Lines. Issue 8 (17th November 2022) - Banerjee, Bidisha
ABSTRACT: Ten years after the publication of Meena Alexander's memoir Fault Lines (1993), she published a revised and expanded edition, including a new Coda where she confronts memories of a childhood trauma, that of being sexually abused by her maternal grandfather. While the original memoir is primarily concerned with her sense of diasporic displacement and the erasures it brings, the 2003 version is concerned with recuperating her lost childhood. What is common to both though are questions of embodiment and the fracturing of the female body. In both instances, writing the self through her body enables Alexander to cope with the fracture; what emerges then is the antithesis of the canonical Self – a deeply fragmented self that must write itself into existence, refashioning herself in new ways through her writing. Alexander's autobiographical writings provide an opportunity to consider the intersections of location and embodiment is diasporic autobiography and the empowering role of writing in countering fragmentations of dislocation and abuse.